(untitled) (Proceedings of the International Conference on Education, 2025)
This study investigates the influence of project-based learning (PBL) on the development of student character within the Cross Cultural Understanding (CCU) framework in Indonesia, using a qualitative research design. PBL is useful in fostering proactive skills, contextual understanding, and technical language competency in a research-focused learning setting. Moreover, engaging in external research and consultancy projects as part of PBL has given students direct academic advantages and improved their behavioral skills and talents, such as communication, confidence, planning, thinking, and time management. In general, PBL provides a distinct set of skills that differ from those normally obtained in traditional teaching and learning settings, making it a viable method for preparing students for success in the modern world. The research includes 15 individuals, including students, instructors, and administrators, chosen by purposive sampling. Data gathering involves conducting interviews with a loose format, observing classrooms, and analyzing documents using NVIVO. Thematic analysis uncovers three main themes: improved teamwork and communication abilities for students, cultural assimilation in PBL for instructors, and comprehensive personal growth for administrators. The results highlight the transforming power of PBL in CCU, promoting inclusive learning settings, cultural relevance, and holistic character development. The study provides valuable information for teachers, government officials, and scholars looking for creative methods to improve education in different cultural settings.